MAKING DYE SENSITIZED SOLAR CELL (DSSC) USING GMR AS SUBSTRACT AND MANGOSTEEN SKIN EXTRACT (Garcinia Mangostana L) AS A DYE SENSITIZER - Dina Wirdatul Ummah; Hary Sanjaya (Departemen Kimia FMIPA UNP, 2019)
The aim of this is to determine the efficiency of DSSC by using GMR as a substrat with mangosteen skin s a dyes. Mangosteen skin contains of anthocyanin pigmentd. Based on the light absorption test of mangosteen peel extract dyes it is known that the spectrum of mangosteen peel can absorb light at the maximum 510 nm wavelength with absorbance of 2.8873 A. The results of the conversion of sunlight into electrical energy obtained the highest value at 50% concentration of 0.281%. Whereas at 5 hours time variation that is equal to 1.053% because ZnO paste is soaked for 5 hours with coloring and drops of liquid electrolyte.